PENGARUH KOMITMEN PROFESIONAL AUDITOR TERHADAP INTENSI MELAKUKAN WHISTLEBLOWING DENGAN RETALIASI SEBAGAI VARIABEL MODERATING (Studi Empiris Pada BRI Provinsi Riau) - Desi Rianti; Azwir Nasir; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of the Auditor Profesional Commitment Against Intention Doing Whistleblowing In retaliation As Moderating Variable. This study uses a quantitative approach. Data collection techniques used is by using a questionnaire instrument. The study was conducted at the BRI Riau Province. Object of research is the perception of all internal auditors on BRI Riau Province about auditor’s proffesional commitmen on Whistleblowing Intention with retaliation as moderating variable. The population in this study are all internal auditors BRI have worked over one year exist in the Riau province. The sampling technique used was purposive sampling with the number of respondents 86 people. Data analysis method used is simple linear regression analysis processed using SPSS 17:00 for Windows. The results showed that (1) the auditor's professional commitment effect on intentions do whistleblowing, with significant value 0.000 <0.05 (2) Commitment to Professional Auditor moderated by retaliation does not affect the intention of doing whistleblowing, with significant value 0.664 <0.05. The coefficient of determination in this study was 19,8%, whereas 80,2% are influenced by variables that are not observed in this research model.Keywords : Auditor’s Proffesional Commitment, Retaliation And Whistleblowing Intention.